Descriptive study of biopsy proven IgA and Henoch-Schonlein purpura nephropathy in two government hospitals in Johannesburg (South Africa) - Mitchell, Jennifer Gwen (My University, 2010)
IgA (Immunoglobulin A) nephropathy is reported as the most common form of primary glomerulonephropathy worldwide. Despite this there is limited research on IgA nephropathy in African children. This study reviewed IgA and Henoch-Schonlein Purpura (HSP) nephropathies, as it is believed that they are variants of the same pathological process. This study hypothesized that IgA and HSP nephropathies occur in South African black children and that disease progression is worse in this population group and compares them to their international counterparts. Methods: The study was a retrospective review of the records of children that presented to the paediatric renal clinics at two academic hospitals in Johannesburg. It reviewed the epidemiology and progression in South African children. These results were then compared to appropriate international reviews. There were a total of 1835 paediatric renal biopsies between 1985 and 2008. Of these 51 were confirmed to be IgA nephropathy (3%) of which one was excluded. Children were reviewed as a whole and then divided into a HSP and an IgA nephropathy group. Results: The average age at presentation was 9.5 years old. There was a male predominance with a male to female ratio of 2.2:1. Racial differences were noted, and when reviewed in the light of the demographics of the area, there was a higher “prevalence” in Caucasian and Indian patients. The most common presenting symptom in the study population was haematuria. Nephrotic range proteinuria occurred in more than half of all patients. Presentation in acute renal iii dysfunction was uncommon. Predictors of a poor prognosis were found to be nephrotic range proteinuria, and a lower GFR at presentation. The study hypothesis that black African children with IgA or HSP nephropathy have a poorer prognosis than other children with similar presentations, was disproved.
MMed (Paediatrics), Faculty of Health Sciences,University of the Witwatersrand
Keywords: kidney disease; children